Islamic banking performance: the interplay of governance, Islamicity performance, and social disclosure - Syafira, Nabila; Soediro, Achmad; Kusumawardani, Media; Pratama, Ahmad (LPPM ISNJ Bengkalis, 2025)
Purpose – This study investigates the influence of Islamic corporate governance (ICG) and the Islamicity performance index (IPI), as proxied by the profit-sharing ratio (PSR), zakat performance ratio (ZPR), and equitable distribution ratio (EDR), on the financial performance of Islamic banks in Indonesia. Furthermore, this study examines the moderating role of Islamic social reporting (ISR) in these relationships. Method – Employing a quantitative approach, this research utilizes secondary data obtained from the Financial Services Authority (FSA) of Indonesia and the official websites of Islamic banks. The sample comprises 10 Islamic commercial banks operating in Indonesia from 2019–2023. The study applies moderated regression analysis (MRA) to assess the proposed relationships. Findings – The findings reveal that, individually, both ICG and EDR positively and significantly influence financial performance, whereas PSR does not exhibit a significant effect. In contrast, ZPR demonstrates a negative and significant impact on financial performance. Moreover, ISR moderates the relationships between ICG, ZPR, and EDR with financial performance, while its moderating effect is not observed in the relationship between PSR and financial performance. ISR strengthens the impact of ICG and the IPI on Islamic banks' financial performance, enhancing the understanding of governance and performance in Islamic finance. Implications – The theoretical implication highlights ISR's role in enhancing ICG and IPI's impact, and the practical implication emphasizes its importance in boosting transparency and trust in Islamic banking.